2016
DOI: 10.1115/1.4033506
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Uncertainty Analysis in Determining Adiabatic Film Cooling Effectiveness by Using Pressure Sensitive Paint Technique

Abstract: While pressure sensitive paint (PSP) technique has been widely used to measure adiabatic film cooling effectiveness distributions on the surfaces of interest based on a mass transfer analog to traditional thermal-based measurements, very little can be found in literature to provide a comprehensive analysis on the uncertainty levels of the measured film cooling effectiveness distributions derived from PSP measurements. In the present study, a detailed analysis is performed to evaluate the effects of various ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It is well known that the uncertainty of measured film cooling effectiveness by using PSP technique is closely related to the PSP calibration process, quality of the acquired raw images, and the flow conditions of the mainstream and coolant streams. Following up the work of Johnson & Hu [28], the absolute measurement uncertainty of the present study was estimated to be within 0.02…”
Section: Figure 3 Experimental Setup Used For Film Cooling Effectivementioning
confidence: 87%
See 2 more Smart Citations
“…It is well known that the uncertainty of measured film cooling effectiveness by using PSP technique is closely related to the PSP calibration process, quality of the acquired raw images, and the flow conditions of the mainstream and coolant streams. Following up the work of Johnson & Hu [28], the absolute measurement uncertainty of the present study was estimated to be within 0.02…”
Section: Figure 3 Experimental Setup Used For Film Cooling Effectivementioning
confidence: 87%
“…In the present study, as suggested by Johnson & Hu [28], a spatially-averaging procedure with interrogation windows of 9×9 pixels and 50% overlap rate was performed for the acquired PSP images, in order to minimize the measurement uncertainties,. Since the acquired PSP images had a magnification of 0.07 mm/pix, the spatial resolution of the PSP measurement results would be about 0.30 mm (i.e., ~ 0.07D).…”
Section: Figure 3 Experimental Setup Used For Film Cooling Effectivementioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the uncertainty of measured film cooling effectiveness by using PSP technique is closely related to PSP calibration process, quality of the acquired raw images, and the flow conditions of the mainstream and coolant streams. Following up the work of Johnson & Hu [22], the absolute measurement uncertainty of the present study was estimated to be within for the measured centerline film cooling effectiveness. The relative measurement uncertainty is estimated to be within 3% for and 5% for .…”
Section: Adiabatic Film Cooling Effectiveness Measurement By Using Psp Techniquementioning
confidence: 99%
“…To know more about this fairly new technique, detailed uncertainty analysis has been performed to evaluate the effects of various uncertainties in PSP measurements on the distribution of  over the surface of interest [11,12]: the main outcome consisted in experimental procedures or guidelines to achieve high-accuracy  measurements. Instead, Wiese et al [13] focused on the suitability of the heat-mass transfer analogy when employing PSP to portray leading edge film cooling.…”
Section: Introductionmentioning
confidence: 99%